2003
DOI: 10.3171/jns.2003.98.3.0491
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular therapy for stenosis of the petrous or cavernous portion of the internal carotid artery: percutaneous transluminal angioplasty compared with stent placement

Abstract: Stent placement is more effective than PTA for stenosis of the petrous or cavernous portion of the ICA from the viewpoint of initial and late gain in diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Only PTA cannot achieve full dilation of petrous lesions because of the surrounding petrous bone. PTA lowered the incidence of restenosis, 18) but elastic recoil and vessel dissection occurred if over-sized PTA balloons were used. 6,21) Technological advances have facilitated the approach to cerebral vessels, and intravascular treatment using balloons and stents has become increasingly safe and effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only PTA cannot achieve full dilation of petrous lesions because of the surrounding petrous bone. PTA lowered the incidence of restenosis, 18) but elastic recoil and vessel dissection occurred if over-sized PTA balloons were used. 6,21) Technological advances have facilitated the approach to cerebral vessels, and intravascular treatment using balloons and stents has become increasingly safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10% of our patients experienced complications after the initial PTA/stent treatment for intracranial stenotic disease; this complication rate agrees with earlier reports. 6,14,17,18,20) An important factor underlying the development of complications was distal embolism during the procedures. Our long-term outcomes were satisfactory and, compared to others, 1,4,10) the re-stenosis rate in our series was low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,14 -24,35-37 Some authors have proposed theoretical advantages of stent placement over primary angioplasty by preventing early elastic recoil and negative remodeling. 38,39 A recent report of a comparison between angioplasty and stent placement in a small group of patients (Nϭ24) suggested that stent placement may be better in terms of early and late lumen gain for intracranial stenosis. 39 No other direct radiographic or clinical outcome comparisons are available in the literature to date.…”
mentioning
confidence: 99%
“…6) To overcome such problems with the balloon catheter, metal stents were introduced with a high expectation, and their effectiveness and favorable therapeutic results have been reported. 7,8) We used coronary stenosis in majority of cases. In the patients reported here, the DWI-positive rate after stenting with flow reversal was 0%, indicating a high preventive effect against distal embolism.…”
Section: Discussionmentioning
confidence: 99%